2020
DOI: 10.1080/09649069.2020.1837517
|View full text |Cite
|
Sign up to set email alerts
|

The role of lawyers in supporting young people in the criminal justice system: balancing economic survival and children’s rights

Abstract: The role of lawyers in supporting young people in the criminal justice system: balancing economic survival and children's rights.Legal aid reductions have caused a crisis in the criminal justice system impacting the quality of representation and advice provided by lawyers. This paper is particularly concerned with the impact of these cuts on young people in the youth criminal justice system. The paper will examine how changes to the way in which defence lawyers are funded is having a damaging impact upon the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Scholars in this area have advocated for increased training for police officers in relation to young people's development, so that they are equipped to deal with young people in a manner that is appropriate to their age and development (Monahan et al, 2015). Lack of adequate training has also been identified as an issue for lawyers, both in the current study and in other jurisdictions (A'Court and Arthur, 2020). The CRC Committee has emphasised the importance of specialised training for all professionals working with children in the youth justice system (Committee on the Rights of the Child, 2019: paras 39, 112).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Scholars in this area have advocated for increased training for police officers in relation to young people's development, so that they are equipped to deal with young people in a manner that is appropriate to their age and development (Monahan et al, 2015). Lack of adequate training has also been identified as an issue for lawyers, both in the current study and in other jurisdictions (A'Court and Arthur, 2020). The CRC Committee has emphasised the importance of specialised training for all professionals working with children in the youth justice system (Committee on the Rights of the Child, 2019: paras 39, 112).…”
Section: Discussionmentioning
confidence: 86%
“…This issue needs careful consideration given the implications for children’s autonomy, as well as the consequences of any delay that might result if the questioning process had to await the arrival of a lawyer. The availability of resources, particularly in relation to legal aid, can impact the way in which legal advice is provided (A’Court and Arthur, 2020). While these issues undoubtedly need to be worked through, given the benefit children can derive from accessing legal advice, this suggestion is worthy of serious examination.…”
Section: Discussionmentioning
confidence: 99%
“…Availing of this assistance also has the potential to increase understanding of their rights and of the potential consequences of the questioning process (Viljoen & Roesch, 2005). Despite these benefits, studies undertaken in a range of jurisdictions have demonstrated that a significant number of children choose not to exercise their right to access legal advice (Schmidt, Reppucci & Woolard, 2003; Viljoen, Klaver & Roesch, 2005); a number of issues, including the potential for delay, can impact children's decision making in this regard (A'Court & Arthur, 2020; Kemp, 2013). This safeguard is protected in a number of ways at domestic level.…”
Section: The Approach Of National Courts In Ireland and New Zealand I...mentioning
confidence: 99%
“…Hence, they are unable to protect themselves from violations of their rights. Therefore, support is needed through legal assistance and other assistance related to increasing access to justice and being child-friendly (A'Court & Arthur, 2020).…”
Section: Introductionmentioning
confidence: 99%